1995
DOI: 10.1055/s-0038-1649923
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C Virus Infection in Haemophilic Patients: Clinical Significance of Viral Genotype

Abstract: SummaryWe have undertaken a comprehensive study of hepatitis C virus (HCV) genotype and its clinical significance in haemophilic patients. 189 HCV RNA positive patients were typed, using the Simmonds classification scheme, by restriction fragment length polymorphism (RFLP) in an amplified segment of the 5 non-coding region of the HCV genome. Type 1 was found in 121 (64.0%), type 2 in 23 (12.2%), type 3 in 36 (19.0%), type 4 in 3 (1.6%), type 5 in 2 (1.1%) and mixed infection in 3 (1.6%). There were no type 6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
(30 reference statements)
2
27
1
Order By: Relevance
“…If there are no doubts about the association between the duration of HCV infection and severity of liver disease, [16][17][18]23,26 more uncertainties exist as to the role of HCV genotype 1 on liver disease progression. [37][38][39][40][41][42][43][44] Our study also confirms for hemophiliacs the observations in non-hemophilic patients 15,18,44 about the greater virulence of genotype 1.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…If there are no doubts about the association between the duration of HCV infection and severity of liver disease, [16][17][18]23,26 more uncertainties exist as to the role of HCV genotype 1 on liver disease progression. [37][38][39][40][41][42][43][44] Our study also confirms for hemophiliacs the observations in non-hemophilic patients 15,18,44 about the greater virulence of genotype 1.…”
Section: Discussionsupporting
confidence: 83%
“…HCV genotype distribution in our cohort of patients is similar to that observed generally in the Italian population 35 and in other studies on hemophiliacs from the same Italian regions, 36,37 but it is quite different from data coming from trials on hemophiliacs in other countries. [38][39][40][41][42][43][44] Furthermore, as hemophiliacs have been exposed to clotting factor concentrates prepared from thousands of donors, some of them have been infected by multiple HCV genotypes. In our study the prevalence of mixed infection is 7% which is similar to that reported in literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that genotype may influence progression of chronic liver disease. Some studies have indicated that HCV genotype 1 is associated with more aggressive liver disease (6,7), but this has not been a consistent finding. In addition to clinical differences, the various genotypes have distinct geographical distributions.…”
Section: Introductionmentioning
confidence: 93%
“…On the basis of nucleotide-sequence homology, the majority of isolates can be classified into 6 major genotypes and a variable number of subtypes [16]. HCV genotype has been shown to be related to responsiveness to interferon [17][18][19] and may have clinical implications with respect to pathogenicity [14,18,[20][21][22].…”
mentioning
confidence: 99%